Jurnal Analisis Analisis manajemen dana: Pengembangan bank syari'ah - Dzakirah, Nabilah Mutiara (Maliki Interdisciplinary Journal, 2024)
Sharia banking fund management is a system where sharia banking financial institutions manage or regulate the position of funds received from financial activities to be channeled into financial activities with the hope that the bank can still meet its needs. its financial liquidity should do that. Profitability and solvency standards. The current development of sharia financial institutions and especially sharia banks cannot be underestimated. Especially regarding sharia banking, its quantitative development and evolution is very encouraging and continues to grow both nationally and internationally. These quantitative developments must be aligned with qualitative developments. The quality of sharia banking is largely determined by the capacity, efficiency and business continuity of sharia banks. The quality of bank investments greatly influences the efficiency and continuity of Islamic banking businesses. Therefore, management of Islamic banks must always follow the principles of prudence and sharia and always maintain the quality of the bank's productive assets to maintain good business performance and development. Fund investment products in the form of funds created by Islamic banks have unique and very different characteristics. However, production asset quality issues must be acknowledged. Because if the quality of the bank's producing assets is maintained then the bank will be a healthy bank. Establishing a healthy sharia bank is the dream of every sharia bank manager. This is possible if bank management can manage sharia bank assets well.